Warga Kerajaan di Dunia Asing: Menavigasi Ketegangan Teologis Antara Hukum Dunia dan Hukum Kerajaan Allah - Tedja Mahananie, Esa (Kaluteros Jurnal Teologi Dan Pendidikan Agama Kristen, 2025)
Christians live within an unavoidable existential tension between the demands of worldly law and the law of God's Kingdom. This article argues that this tension is not a problem to be eliminated, but rather the space in which authentic Christian discipleship occurs. Adopting a theological framework that synthesizes three main pillars, this study offers a path for navigating this dilemma. First, George Eldon Ladd's "already and not yet" eschatology is employed to understand God's Kingdom as divine reign that has dynamically arrived in Christ, yet has not reached its fullness. Second, the radical ethics of the Sermon on the Mount (Matthew 5–7) are analyzed as the constitution or fundamental law of that Kingdom, emphasizing inner righteousness and love that transcend worldly legalism. Third, the countercultural ecclesiology of Stanley Hauerwas and William Willimon presents the Church as the most significant political response not through direct transformation of the state, but by embodying itself as an alternative "colony" living under the Kingdom's law. The main thesis of this article is that the most faithful Christian response to the conflict between these two laws is neither compromise ("cheap grace") nor isolationism, but rather the embodiment of the Church as a visible community that, through its distinctive way of life, becomes a powerful prophetic witness to the world.